The construction of female characters in the selected Grimm Brothers' fairy tales - Shahwan, Tasneem Rasheed
Gender roles are one of the elements that differentiate modern and traditional literature. This research discusses the construction of female characters in Grimm Brothers' fairy tales which are Cinderella, Snow White, Little Red Riding Hood, and Sleeping Beauty. In these fairy tales, there is a skewed discrimination of female characters based on their roles in society. In this qualitative study, the fairy tales were selected using purposive sampling on the basis that they are relevant sources from Grim Brothers which can provide clear insights into the biased construction of female characters. The texts were approached from a social feminism perspective and analysed using thematic analysis. The main finding is that women had limited gender roles confined in the homestead. Authors' portrayals of the female characters create discrimination based on their domestic purposes. Power relations between mal and female characters in the fairy tales show that male characters have stronger economic, social and political power compared to female characters. Male characters have authority over female characters making them superior in the society. The fairy tales also present female characters as having peculiar characters compared to male character . Female characters have dominant characters of being naive, gullible, weak and stupid. Whereas the male characters have superior traits such as being strong, intelligent and wise. The authors present female characters with unique social characteristics making them diff r nt from male characters. Female characters have social characteristics such as caring, housewife, selfish and weak. The ocial characters of women subjected them to male authority in the ociety. The power relation and characteristics of women in the fairy tales shows female discrimination by a male-dominant society. The analysis on the construction offemale characters in Grimm Brothers' fairy tales helps to understand the challenges of women in the society. This research is hoped to contribute to the efforts in empowering women by identifying their challenges in the society. It is recommended that future literary authors need to write texts that presents both women and men as equal players in the society with unlimited roles.